In the country of illness : comfort and advice for the journey - Lipsyte, Robert (Alfred Knopf, 1998)
To help us cope with, and ease, the experience of serious illness - our own illness or that of someone we care about - is the purpose of Robert Lipsyte's fascinating and bracing book. He offers invaluable practical advice for patients and for the people close to them.